Wash-off behaviour of seven different sunscreens assessed with a novel skin application method - Julia Rücker; Leon Brück; Hannah Herschke; Claire Schell; Lasse Schacht; Benjamin Mueller; Arjen Tilstra; Moira S. McKee; Michael Sweet; Christian Wild (Marine Environmental Research, 2026)

Monitoring ketamine use and evaluating its persistence across 106 wastewater treatment plants in Australia - Zeyang Zhao; Rory Verhagen; Jake W. O’Brien; Benjamin J. Tscharke; Jinglong Li; Zhe Wang; Qiuda Zheng; Emma L. Keller; Jochen F. Mueller; Phong K. Thai (Journal of Water Process Engineering, 2026)

Interactive effects of manganese addition and simulated ocean warming differ between hard and soft corals - Thilo Appeldorn; Marlen Matthäs; Julius Krebs; Sören Völker; Ekkehard Küstermann; Benjamin Mueller; Bianca Maria Thobor; Christian Wild (Frontiers in Marine Science, 2026)
Marine heat waves pose a critical threat to hard corals and mitigation strategies are needed to support coral survival. Manganese (Mn) is an essential micronutrient whose addition can alleviate thermal stress in some hard corals. However, the effective dose as well as potential detrimental effects at higher dosages are largely unknown and may be species-specific. To assess the suitability of Mn supplementation as an intervention measure, it is further crucial to test its effect on other coral reef organisms, such as soft corals. We investigated the combined effect of Mn supplementation (daily pulses of 0, 120 and 260 µg L -1 ) during a simulated heatwave (stepwise increase from 26 to 32 °C) on the physiology of the hard coral Montipora digitata and the pulsating soft coral Xenia umbellata in a 5-week aquarium experiment. Mn addition did not have a significant effect on both corals at the culture temperature of 26 °C. M. digitata was increasingly affected by rising temperatures with severe bleaching and a 90% reduction in symbiont density at 32 °C, independent of Mn concentration. In contrast, X. umbellata was unaffected by increasing temperature alone, but in combination with Mn enrichment, polyp pulsation was reduced by 20% (120 µg L -1 ) and 44% (260 µg L -1 ) over the last week at 32 °C, respectively. Corroborative semi-quantitative MRI measurements further indicated a higher Mn incorporation by X. umbellata compared to M. digitata , suggesting species-specific differences in trace metal accumulation. These findings emphasize the importance of species-specific differences in hard corals and other coral reef organisms, when assessing the potential of Mn enrichment as an intervention measure to increase heat resistance in hard corals.

Utilizing national wastewater and sales data to derive and validate the correction factors of five common antidepressants for wastewater-based epidemiology - Zeyang Zhao; Jingyi Yuan; Qiuda Zheng; Benjamin J. Tscharke; Tim Boogaerts; Zhe Wang; Shuo Chen; Jake W. O'Brien; Alexander L.N. van Nuijs; Adrian Covaci; Jochen Mueller; Phong K. Thai (Water Research, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Microbiological risk factors, ICU survival, and 1-year survival in hematological patients with pneumonia requiring invasive mechanical ventilation - Benjamin Seybold; Timo Funk; Peter Dreger; Gerlinde Egerer; Juliane Brandt; Carsten Mueller-Tidow; Nicola Giesen; Uta Merle (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose To identify pathogenic microorganisms and microbiological risk factors causing high morbidity and mortality in immunocompromised patients requiring invasive mechanical ventilation due to pneumonia. Methods A retrospective single-center study was performed at the intensive care unit (ICU) of the Department of Internal Medicine at Heidelberg University Hospital (Germany) including 246 consecutive patients with hematological malignancies requiring invasive mechanical ventilation due to pneumonia from 08/2004 to 07/2016. Microbiological and radiological data were collected and statistically analyzed for risk factors for ICU and 1-year mortality. Results ICU and 1-year mortality were 63.0% (155/246) and 81.0% (196/242), respectively. Pneumonia causing pathogens were identified in 143 (58.1%) patients, multimicrobial infections were present in 51 (20.7%) patients. Fungal, bacterial and viral pathogens were detected in 89 (36.2%), 55 (22.4%) and 41 (16.7%) patients, respectively. Human herpesviruses were concomitantly reactivated in 85 (34.6%) patients. As significant microbiological risk factors for ICU mortality probable invasive Aspergillus disease with positive serum-Galactomannan (odds ratio 3.1 (1.2-8.0), p = 0.021,) and pulmonary Cytomegalovirus reactivation at intubation (odds ratio 5.3 (1.1–26.8), p = 0.043,) were identified. 1-year mortality was not significantly associated with type of infection. Of interest, 19 patients had infections with various respiratory viruses and Aspergillus spp. superinfections and experienced high ICU and 1-year mortality of 78.9% (15/19) and 89.5% (17/19), respectively. Conclusions Patients with hematological malignancies requiring invasive mechanical ventilation due to pneumonia showed high ICU and 1-year mortality. Pulmonary Aspergillosis and pulmonary reactivation of Cytomegalovirus at intubation were significantly associated with negative outcome.

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Monitoring the use of novel psychoactive substances in Australia by wastewater-based epidemiology - Emma L. Jaunay; Richard Bade; Kara R. Paxton; Dhayaalini Nadarajan; Daniel C. Barry; Yuze Zhai; Benjamin J. Tscharke; Jake W. O'Brien; Jochen Mueller; Jason M. White; Bradley S. Simpson; Cobus Gerber (Science of The Total Environment, 2024)

Sponges on shifting reefs: holobionts show similar molecular and physiological responses to coral versus macroalgal food - Sara Campana; Milou G. I. Arts; Cristina Díez-Vives; Benjamin Mueller; Corinna Bang; Ana Riesgo; Andreas F. Haas; Gerard Muyzer; Jasper M. de Goeij (Frontiers in Marine Science, 2024)
Introduction Many coral reefs witness an ongoing coral-to-algae phase shift. Corals and algae release large quantities of (in)organic nutrients daily, of which a large part is utilized by sponges. In turn, sponges are important cyclers of precious resources to other inhabitants on reefs residing in oligotrophic waters. Here, we investigated whether sponge holobionts (i.e., host and prokaryotic symbionts) adapt their physiology to food released by coral- versus macroalgae. Methods Thereto, two sponge species, Plakortis angulospiculatus and Halisarca caerulea (high and low microbial abundance, respectively), were continuously exposed for 12 days to coral and macroalgal exudates in running seawater aquaria. Transcript expression of host and prokaryotic symbionts, changes in prokaryotic community composition, and holobiont physiological responses (i.e., respiratory demand, fluxes of carbon and nitrogen) were investigated after coral- versus macroalgae dominated treatments and compared to a seawater only control treatment. Results In both sponge holobionts differential transcript expression between the coral and macroalgae treatments was very low (<0.01% of total transcripts). Differential expression was found in genes targeting cellular signaling pathways, e.g., cell proliferation (upregulated in coral treatment), and immune response (upregulated in macroalgal treatment). The sponge-associated prokaryotic community composition and sponge physiological responses were similar in all treatments, yet differed significantly between the two species. Discussion After 12 days of exposure sponges appear to opportunistically feed on different food sources without having to adjust their metabolic pathways or associated prokaryotic communities. This suggests that sponges could be well-adapted to predicted changes in food source availability due to coral-to-algal phase shifts on many coral reefs.

Analysis of wastewater from 2013 to 2021 detected a recent increase in nicotine use in Queensland, Australia - Zhe Wang; Qiuda Zheng; Jake W. O'Brien; Benjamin J. Tscharke; Gary Chan; Kevin V. Thomas; Jochen F. Mueller; Phong K. Thai (Water Research, 2024)

Exploring drug consumption patterns across varying levels of remoteness in Australia - Rory Verhagen; Sarit L. Kaserzon; Kevin V. Thomas; Jochen F. Mueller; Benjamin J. Tscharke (Science of The Total Environment, 2023)

Bisphenols and phthalates in Australian wastewater: A statistical approach for estimating contributions from diffuse and point sources - Belinda Moore; Chang He; Emma Knight; Jochen F. Mueller; Benjamin Tscharke (Water Research, 2023)

Monitoring medication and illicit drug consumption in a prison by wastewater-based epidemiology: Impact of COVID-19 restrictions - Zhe Wang; Jochen F. Mueller; Jake W. O'Brien; Jack Thompson; Benjamin J. Tscharke; Rory Verhagen; Qiuda Zheng; Jeremy Prichard; Wayne Hall; Keith Humphreys; Kevin V. Thomas; Phong K. Thai (Water Research, 2023)

Small-scale oxygen distribution patterns in a coral reef - Adam S. Candy; Shannara K. Taylor Parkins; Fleur C. Van Duyl; Benjamin Mueller; Milou G. I. Arts; Will Barnes; Marie Carstensen; Yun J. H. Scholten; Yusuf C. El-Khaled; Christian Wild; Linda Wegley Kelly; Craig E. Nelson; et al. (Frontiers in Marine Science, 2023)
One mechanism giving fleshy algae a competitive advantage over corals during reef degradation is algal-induced and microbially-mediated hypoxia (typically less than 69.5 µmol oxygen L −1 ). During hypoxic conditions oxygen availability becomes insufficient to sustain aerobic respiration in most metazoans. Algae are more tolerant of low oxygen conditions and may outcompete corals weakened by hypoxia. A key question on the ecological importance of this mechanism remains unanswered: How extensive are local hypoxic zones in highly turbulent aquatic environments, continuously flushed by currents and wave surge? To better understand the concert of biological, chemical, and physical factors that determine the abundance and distribution of oxygen in this environment, we combined 3D imagery, flow measurements, macro- and micro-organismal abundance estimates, and experimentally determined biogenic oxygen and carbon fluxes as input values for a 3D bio-physical model. The model was first developed and verified for controlled flume experiments containing coral and algal colonies in direct interaction. We then developed a three-dimensional numerical model of an existing coral reef plot off the coast of Curaçao where oxygen concentrations for comparison were collected in a small-scale grid using fiberoptic oxygen optodes. Oxygen distribution patterns given by the model were a good predictor for in situ concentrations and indicate widespread localized differences exceeding 50 µmol L -1 over distances less than a decimeter. This suggests that small-scale hypoxic zones can persist for an extended period of time in the turbulent environment of a wave- and surge- exposed coral reef. This work highlights how the combination of three-dimensional imagery, biogenic fluxes, and fluid dynamic modeling can provide a powerful tool to illustrate and predict the distribution of analytes (e.g., oxygen or other bioactive substances) in a highly complex system.

Sponge holobionts shift their prokaryotic communities and antimicrobial activity from shallow to lower mesophotic depths - Anak Agung Gede Indraningrat; Georg Steinert; Leontine E. Becking; Benjamin Mueller; Jasper M. de Goeij; Hauke Smidt; Detmer Sipkema (Antonie van Leeuwenhoek, 2022)
In this study, we used 16S rRNA gene amplicon sequencing to investigate prokaryotic community composition of the Caribbean sponges Xestospongia muta and Agelas sventres from three depth ranges: X. muta was enriched in Cyanobacteria, Chloroflexota, and Crenarchaeota compared to samples from mesophotic depths, while mesophotic samples of X. muta were enriched in Acidobacteriota. For A. sventres , relative abundance of Acidobacteriota, Chloroflexota, and Gammaproteobacteria was higher in shallow samples, while Proteobacteria and Crenarchaeota were enriched in mesophotic A. sventres samples. Antimicrobial activity was evaluated by screening crude extracts of sponges against a set of Gram-positive and Gram-negative bacteria, a yeast, and an oomycete. Antibacterial activities from crude extracts of shallow sponge individuals were generally higher than observed from mesophotic individuals, that showed limited or no antibacterial activities. Conversely, the highest anti-oomycete activity was found from crude extracts of X. muta individuals from lower mesophotic depth, but without a clear pattern across the depth gradient. These results indicate that sponge-associated prokaryotic communities and the antimicrobial activity of sponges change within species across a depth gradient from shallow to mesophotic depth.

Implications of 2D versus 3D surveys to measure the abundance and composition of benthic coral reef communities - Niklas A. Kornder; Jose Cappelletto; Benjamin Mueller; Margaretha J. L. Zalm; Stephanie J. Martinez; Mark J. A. Vermeij; Jef Huisman; Jasper M. de Goeij (Coral Reefs, 2021)
A paramount challenge in coral reef ecology is to estimate the abundance and composition of the communities residing in such complex ecosystems. Traditional 2D projected surface cover estimates neglect the 3D structure of reefs and reef organisms, overlook communities residing in cryptic reef habitats (e.g., overhangs, cavities), and thus may fail to represent biomass estimates needed to assess trophic ecology and reef function. Here, we surveyed the 3D surface cover, biovolume, and biomass (i.e., ash-free dry weight) of all major benthic taxa on 12 coral reef stations on the island of Curaçao (Southern Caribbean) using structure-from-motion photogrammetry, coral point counts, in situ measurements, and elemental analysis. We then compared our 3D benthic community estimates to corresponding estimates of traditional 2D projected surface cover to explore the differences in benthic community composition using different metrics. Overall, 2D cover was dominated (52 ± 2%, mean ± SE) by non-calcifying phototrophs (macroalgae, turf algae, benthic cyanobacterial mats), but their contribution to total reef biomass was minor (3.2 ± 0.6%). In contrast, coral cover (32 ± 2%) more closely resembled coral biomass (27 ± 6%). The relative contribution of erect organisms, such as gorgonians and massive sponges, to 2D cover was twofold and 11-fold lower, respectively, than their contribution to reef biomass. Cryptic surface area (3.3 ± 0.2 m 2 m −2 planar reef ) comprised half of the total reef substrate, rendering two thirds of coralline algae and almost all encrusting sponges (99.8%) undetected in traditional assessments. Yet, encrusting sponges dominated reef biomass (35 ± 18%). Based on our quantification of exposed and cryptic reef communities using different metrics, we suggest adjustments to current monitoring approaches and highlight ramifications for evaluating the ecological contributions of different taxa to overall reef function. To this end, our metric conversions can complement other benthic assessments to generate non-invasive estimates of the biovolume, biomass, and elemental composition (i.e., standing stocks of organic carbon and nitrogen) of Caribbean coral reef communities.

Processing of Naturally Sourced Macroalgal- and Coral-Dissolved Organic Matter (DOM) by High and Low Microbial Abundance Encrusting Sponges - Sara Campana; Meggie Hudspith; David Lankes; Anna de Kluijver; Celine Demey; Jorien Schoorl; Samira Absalah; Marcel T. J. van der Meer; Benjamin Mueller; Jasper M. de Goeij (Frontiers in Marine Science, 2021)
Sponges play a key role in (re)cycling of dissolved organic matter (DOM) and inorganic nutrients in coral reef ecosystems. Macroalgae and corals release different quantities of DOM and at different bioavailabilities to sponges and their microbiome. Given the current coral- to algal-dominance shift on coral reefs, we assessed the differential processing of macroalgal- and coral-DOM by three high and three low microbial abundance (HMA and LMA) encrusting sponge species. We followed the assimilation of naturally sourced 13 C- and 15 N-enriched macroalgal- and coral-DOM into bulk tissue and into host- versus bacteria-specific phospholipid fatty acids (PLFAs). Additionally, we compared sponge-processing of the two natural DOM sources with 13 C- and 15 N-enriched laboratory-made diatom-DOM. All investigated sponges utilized all DOM sources, with higher assimilation rates in LMA compared to HMA sponges. No difference was found in carbon assimilation of coral- versus macroalgal-DOM into bulk tissue and host- versus bacteria-specific PLFAs, but macroalgal nitrogen was assimilated into bulk tissue up to eight times faster compared to the other sources, indicating its higher bioavailability to the sponges. Additionally, LMA sponges released significantly more inorganic nitrogen after feeding on macroalgal-DOM. Therefore, we hypothesize that, depending on the abundance and composition of the sponge community, sponges could catalyze reef eutrophication through increased turnover of nitrogen under coral-to-algal regime shifts.

Comparative toxicity assessment of in situ burn residues to initial and dispersed heavy fuel oil using zebrafish embryos as test organisms - Sarah Johann; Mira Goßen; Leonie Mueller; Valentina Selja; Kim Gustavson; Janne Fritt-Rasmussen; Susse Wegeberg; Tomasz Maciej Ciesielski; Bjørn Munro Jenssen; Henner Hollert; Thomas-Benjamin Seiler (Environmental Science and Pollution Research, 2021)
In situ burning (ISB) is discussed to be one of the most suitable response strategies to combat oil spills in extreme conditions. After burning, a highly viscous and sticky residue is left and may over time pose a risk of exposing aquatic biota to toxic oil compounds. Scientific information about the impact of burn residues on the environment is scarce. In this context, a comprehensive ISB field experiment with approx. 1000L IFO 180 was conducted in a fjord in Greenland. The present study investigated the toxicity of collected ISB residues to early life stages of zebrafish ( Danio rerio ) as a model for potentially exposed pelagic organisms. The toxicity of ISB residues on zebrafish embryos was compared with the toxicity of the initial (unweathered) IFO 180 and chemically dispersed IFO 180. Morphological malformations, hatching success, swimming behavior, and biomarkers for exposure (CYP1A activity, AChE inhibition) were evaluated in order to cover the toxic response on different biological organization levels. Across all endpoints, ISB residues did not induce greater toxicity in zebrafish embryos compared with the initial oil. The application of a chemical dispersant increased the acute toxicity most likely due to a higher bioavailability of dissolved and particulate oil components. The results provide insight into the adverse effects of ISB residues on sensitive life stages of fish in comparison with chemical dispersant application.

Three-Dimensional Molecular Cartography of the Caribbean Reef-Building Coral Orbicella faveolata - Mark Little; Emma E. George; Milou G. I. Arts; Jade Shivak; Sean Benler; Joel Huckeba; Zachary A. Quinlan; Vittorio Boscaro; Benjamin Mueller; Ana Georgina Cobián Güemes; Maria Isabel Rojas; Brandie White; et al. (Frontiers in Marine Science, 2021)
All organisms host a diversity of associated viruses, bacteria, and protists, collectively defined as the holobiont. While scientific advancements have enhanced the understanding of the functional roles played by various components of the holobiont, there is a growing need to integrate multiple types of molecular data into spatially and temporally resolved frameworks. To that end, we mapped 16S and 18S rDNA metabarcoding, metatranscriptomics, and metabolomic data onto three-dimensional reconstructions of coral colonies to examine microbial diversity, microbial gene expression, and biochemistry on two colonies of the ecologically important, reef-building coral, Orbicella faveolata and their competitors (i.e., adjacent organisms interacting with the corals: fleshy algae, turf algae, hydrozoans, and other corals). Overall, no statistically significant spatial patterns were observed among the samples for any of the data types; instead, strong signatures of the macroorganismal hosts (e.g., coral, algae, hydrozoa) were detected, in the microbiome, the transcriptome, and the metabolome. The 16S rDNA analysis demonstrated higher abundance of Firmicutes in the coral microbiome than in its competitors. A single bacterial amplicon sequence variant from the genus Clostridium was found exclusively in all O. faveolata samples. In contrast to microbial taxa, a portion of the functionally annotated bacterial RNA transcripts (6.86%) and metabolites (1.95%) were ubiquitous in all coral and competitor samples. Machine learning analysis of microbial transcripts revealed elevated T7-like cyanophage-encoded photosystem II transcripts in O. faveolata samples, while sequences involved in bacterial cell division were elevated in turf algal and interface samples. Similar analysis of metabolites revealed that bacterial-produced antimicrobial and antifungal compounds were highly enriched in coral samples. This study provides insight into the spatial and biological patterning of the coral microbiome, transcriptome, and metabolome.

Dissolved organic carbon ( DOC ) is essential to balance the metabolic demands of four dominant North‐Atlantic deep‐sea sponges - Martijn C. Bart; Benjamin Mueller; Titus Rombouts; Clea van de Ven; Gabrielle J. Tompkins; Ronald Osinga; Corina P.D. Brussaard; Barry MacDonald; Anja Engel; Hans Tore Rapp; Jasper M. de Goeij (Limnology and Oceanography, 2021)
Sponges are ubiquitous components of various deep‐sea habitats, including cold water coral reefs, and form deep‐sea sponge grounds. Although the deep sea is generally considered to be a food‐limited environment, these ecosystems are known to be hotspots of biodiversity and carbon cycling. To assess the role of sponges in the carbon cycling of deep‐sea ecosystems, we studied the carbon budgets of six dominant deep‐sea sponges of different phylogenetic origin, with various growth forms and hosting distinct associated microbial communities, in an ex situ aquarium setup. Additionally, we determined biomass metrics—planar surface area, volume, wet weight, dry weight (DW), ash‐free dry weight, and organic carbon (C) content—and conversion factors for all species. Oxygen (O 2 ) removal rates averaged 3.3 ± 2.8 μ mol O 2 g DW sponge h −1 (mean ± SD), live particulate (bacterio‐ and phytoplankton) organic carbon removal rates averaged 0.30 ± 0.39 μ mol C g DW sponge h −1 and dissolved organic carbon (DOC) removal rates averaged 18.70 ± 25.02 μ mol C g DW sponge h −1 . Carbon mass balances were calculated for four species and revealed that the sponges acquired 1.3–6.6 times the amount of carbon needed to sustain their minimal respiratory demands. These results indicate that irrespective of taxonomic class, growth form, and abundance of microbial symbionts, DOC is responsible for over 90% of the total net organic carbon removal of deep‐sea sponges and allows them to sustain themselves in otherwise food‐limited environments on the ocean floor.

Depth‐dependent detritus production in the sponge, Halisarca caerulea - Michael P. Lesser; Benjamin Mueller; M. Sabrina Pankey; Keir J. Macartney; Marc Slattery; Jasper M. de Goeij (Limnology and Oceanography, 2020)
Sponges are important ecological and functional components of coral reefs. Recently, a new hypothesis about the functional ecology of sponges in organic matter recycling pathways, the sponge‐loop hypothesis, in which dissolved and particulate organic matter is taken up by sponges and shunted to higher trophic levels as detritus, has been proposed and demonstrated for shallow ( Halisarca caerulea from water depths of 10 and 50 m. Detritus production was significantly lower in mesophotic sponges compared to shallow samples of H. caerulea . Additionally, detritus production rates in transplanted sponges moved in the direction of rates observed for resident conspecifics. The microbiome of these sponge populations was also significantly different between shallow and mesophotic depths, and the microbial communities of the transplanted sponges also shifted in the direction of their new depth in 10 d largely driven by changes in Oxyphotobacteria , Acidimicrobiia , Nitrososphaeria , Nitrospira , Deltaproteobacteria , and Dadabacteriia . This occurred in an environment where the availability of both dissolved and particulate trophic resources changed significantly across the shallow to mesophotic depth gradient where these sponge populations were found. These results suggest that changes in sponge detritus production are primarily driven by differential quality and quantity of trophic resources, as well as their utilization by the sponge host, and its microbiome, along the shallow to mesophotic depth gradient.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Higher order total variation regularization for EIT reconstruction - Bo Gong; Benjamin Schullcke; Sabine Krueger-Ziolek; Fan Zhang; Ullrich Mueller-Lisse; Knut Moeller (Medical & Biological Engineering & Computing, 2018)

Cognitive and emotional demands of black humour processing: the role of intelligence, aggressiveness and mood - Ulrike Willinger; Andreas Hergovich; Michaela Schmoeger; Matthias Deckert; Susanne Stoettner; Iris Bunda; Andrea Witting; Melanie Seidler; Reinhilde Moser; Stefanie Kacena; David Jaeckle; Benjamin Loader; et al. (Cognitive Processing, 2017)

Enhanced aphid abundance in spring desynchronizes predator–prey and plant–microorganism interactions - Benjamin Fuchs; Tatjana Breuer; Simone Findling; Markus Krischke; Martin J. Mueller; Andrea Holzschuh; Jochen Krauss (Oecologia, 2017)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Peramine and Lolitrem B from Endophyte-Grass Associations Cascade Up the Food Chain - Benjamin Fuchs; Markus Krischke; Martin J. Mueller; Jochen Krauss (Journal of Chemical Ecology, 2013)

Size at maturation, sex differences, and pair density during the mating season of the Indo-Pacific beach star Archaster typicus (Echinodermata: Asteroidea) in the Philippines - Arthur R. Bos; Girley S. Gumanao; Benjamin Mueller; Marjho M. Saceda (Invertebrate Reproduction & Development, 2013)

Ontogenetic habitat shift, population growth, and burrowing behavior of the Indo-Pacific beach star, Archaster typicus (Echinodermata; Asteroidea) - Arthur R. Bos; Girley S. Gumanao; Marieke M. van Katwijk; Benjamin Mueller; Marjho M. Saceda; Rosie Lynn P. Tejada (Marine Biology, 2011)

Genetic determinants of acenocoumarol and phenprocoumon maintenance dose requirements - Janne Cadamuro; Benjamin Dieplinger; Thomas Felder; Igor Kedenko; Thomas Mueller; Meinhard Haltmayer; Wolfgang Patsch; Hannes Oberkofler (European Journal of Clinical Pharmacology, 2010)

Intestinal macrophages: differentiation and involvement in intestinal immunopathologies - Benjamin Weber; Leslie Saurer; Christoph Mueller (Seminars in Immunopathology, 2009)